Radical‐Bridged Heterometallic Single‐Molecule Magnets Incorporating Four Lanthanoceniums. Issue 12 (14th February 2023) - Zhang, Peng; Luo, Qian‐Cheng; Zhu, Zhenhua; He, Wanrong; Song, Nan; Lv, Junting; Wang, Xuning; Zhai, Quan‐Guo; Zheng, Yan‐Zhen; Tang, Jinkui
Abstract: The syntheses and magnetic properties of organometallic heterometallic compounds [K(THF)6 ]{Co I [( μ 3 ‐HAN)RE2 Cp*4 ]2 } (1‐RE ) and [K(Crypt)]2 {Co I [( μ 3 ‐HAN)RE2 Cp*4 ]2 } (2‐RE ) containing hexaazatrinaphthylene radicals (HAN⋅ 3− ) and four rare earth (RE) ions are reported. 1‐RE shows isolable species with ligand‐based mixed valency as revealed by cyclic voltammetry (CV) thus leading to the isolation of 2‐RE via one‐electron chemical reduction. Strong electronic communication in mixed‐valency supports stronger overall ferromagnetic behaviors in 2‐RE than 1‐RE containing Gd and Dy ions. Ac magnetic susceptibility data reveal 1‐Dy and 2‐Dy both exhibit slow magnetic relaxation. Importantly, larger coercive field was observed in the hysteresis of 2‐Dy at 2.0 K, indicating the enhanced SMM behavior compared with 1‐Dy . Ligand‐based mixed‐valency strategy has been used for the first time to improve the magnetic coupling in lanthanide (Ln) SMMs, thus opening up new ways to construct strongly coupled Ln‐SMMs. Abstract : Radical‐bridged organometallic heterometallic single‐molecule magnets (SMMs) were isolated for the first time, representing a new class of organometallic lanthanide (Ln) SMMs. The novel strategy effectively overcomes the limited number of metal centers in radical‐bridged Ln‐SMMs, opening up new ways to construct larger strongly coupled Ln‐SMMs.